Intention to vaccinate against COVID-19 and adherence to non-pharmaceutical interventions against COVID-19 prior to the second wave of the pandemic in Uganda: a cross-sectional study. Issue 6 (2nd June 2022) - Wafula, Solomon Tsebeni; Mugume, Innocent B; Sensasi, Benjamin; Okware, Solome; Chimbaru, Alexander; Nanyunja, Miriam; Talisuna, Ambrose; Kabanda, Richard; Bakyaita, Tabley; Wanyenze, Rhoda K; Byakika-Tusiime, Jayne
Abstract : Objectives: The resurgence in cases and deaths due to COVID-19 in many countries suggests complacency in adhering to COVID-19 preventive guidelines. Vaccination, therefore, remains a key intervention in mitigating the impact of the COVID-19 pandemic. This study investigated the level of adherence to COVID-19 preventive measures and intention to receive the COVID-19 vaccine among Ugandans. Design, setting and participants: A nationwide cross-sectional survey of 1053 Ugandan adults was conducted in March 2021 using telephone interviews. Main outcome measures: Participants reported on adherence to COVID-19 preventive measures and intention to be vaccinated with COVID-19 vaccines. Results: Overall, 10.2% of the respondents adhered to the COVID-19 preventive guidelines and 57.8% stated definite intention to receive a SARS-CoV-2 vaccine. Compared with women, men were less likely to adhere to COVID-19 guidelines (Odds Ratio (OR)=0.64, 95% CI 0.41 to 0.99). Participants from the northern (4.0%, OR=0.28, 95% CI 0.12 to 0.92), western (5.1%, OR=0.30, 95% CI 0.14 to 0.65) and eastern regions (6.5%, OR=0.47, 95% CI 0.24 to 0.92), respectively, had lower odds of adhering to the COVID-19 guidelines than those from the central region (14.7%). A higher monthly income of ≥US$137 (OR=2.31, 95% CI 1.14 to 4.58) and a history of chronic disease (OR=1.81, 95% CI 1.14 to 2.86) were predictors of adherence. Concerns about the chances of getting COVID-19 in the future (Prevalence Ratio (PR)=1.26, 95% CI 1.06 to 1.48) and fear of severe COVID-19 infection (PR=1.20, 95% CI 1.04 to 1.38) were the strongest predictors for a definite intention, while concerns for side effects were negatively associated with vaccination intent (PR=0.75, 95% CI 0.68 to 0.83). Conclusion: Behaviour change programmes need to be strengthened to promote adherence to COVID-19 preventive guidelines as vaccination is rolled out as another preventive measure. Dissemination of accurate, safe and efficacious information about the vaccines is necessary to enhance vaccine uptake.